Intermittent fasting as a treatment for obesity in young people: a scoping review - Jomanah Bakhsh; Sarah-Jeanne Salvy; Alaina P. Vidmar (npj Metabolic Health and Disease)
Abstract Intermittent fasting focuses on the timing of eating rather than diet quality or energy intake, with evidence supporting its effects on weight loss and improvements in cardiometabolic outcomes in adults with obesity. However, there is limited evidence for its feasibility and efficacy in young people. To address this, a scoping review was conducted to examine intermittent fasting regimens in individuals aged 10 to 25 for the treatment of obesity focusing on methodology, intervention parameters, outcomes, adherence, feasibility, and efficacy. Due to the paucity of evidence in this age group, to adequately assess feasibility and adherence, all published studies of intermittent fasting in this age category, regardless of weight status and treatment intention, were included in the review. The review included 34 studies (28 interventional studies and 6 observational studies) with 893 participants aged 12 to 25. Interventions varied with 9 studies in cohorts with obesity utilizing intermittent fasting as an obesity treatment. Thirteen studies utilized 8-h time-restricted eating. Primary outcomes included cardiometabolic risk factors (7/28), anthropometric measurements (7/28), body composition (5/28), muscular performance (4/28), feasibility (1/28), and others (4/28). All 9 studies conducted in young people with obesity reported some degree of weight loss, although the comparator groups varied significantly. This review underscores the various utilizations of intermittent fasting in this age group and highlights its potential in treating obesity. However, the findings emphasize the need for rigorous studies with standardized frameworks for feasibility to ensure comparability and determine intermittent fasting’s practicality in this age group depending on the treatment outcome of interest.